Main Drivers Shaping Iran's Foreign Policy Under Mahmoud Ahmadinejad and Hassan Rouhani: Iraq as a Case Study (2005-2021) - Mohammed, Zebar Azeez; Ahmad, Dr. Mahdi Mostafa Faqi (Journal of Legal and Political Studies, 2025)
This study examines the main drivers that formulated Iran's foreign policy under Mahmoud Ahmadinejad and Hassan Rouhani: Iraq as a case study (2005-2021). The importance of this is that Iran is a revisionist state and has a strong presence in the political equation in Iraq. The study also reveals the main Drivers behind Iran's foreign policy towards Iraq under Ahmadinejad and Rouhani. The study used analytical-qualitative methods and implemented the structural realism theory. As a result, the study found several main drivers that influenced Iran's foreign policy during this period: political, security, ideological, economic, and regional. However, security and ideology are the most influential of these primary drivers under Ahmadinejad. During Rouhani's tenure, security, economic, and regional Drivers have been more influential than others. These Drivers mostly reacted to the international system's anarchy, which equally encouraged states to pursue increased power, security, and survival. These Drivers had a direct impact on Iran's growing role in Iraq, and the balance of power was mainly in Iran's interest, eventually turning Iran into a semi-state Dominant in Iraq. Keywords: The Islamic Republic of Iran, Iraq, Foreign policy, Drivers, Power.
Keywords: Keywords The Islamic Republic of Iran; Iraq; Foreign policy; Drivers; Power